Structural insights into viral RNA capping and plasma membrane targeting by Chikungunya virus nonstructural protein 1 - Zhang, Kuo (2022)
Chikungunya virus (CHIKV) causes a debilitating arthralgic inflammatory disease in humans. The multifunctional CHIKV protein, nsP1, facilitates virus RNA replication and transcription by anchoring the viral replication complex (RC) to plasma membrane vesicles and synthesizing the viral RNA 5' cap-0. Here, we report a cryo-EM structure of CHIKV nsP1 at 2.38 Å resolution. Twelve copies of nsP1 form a crown-shaped ring structure with a 7.5-nm-wide channel for mediating communication and exchange between the viral RC and the host cell. The catalytic site for viral RNA capping is located in a tunnel that is shaped by neighboring nsP1 molecules. Two membrane-association loops target nsP1 to the inner leaflet of the plasma membrane via palmitoylation and hydrophobic and electrostatic interactions. Our study provides the structural basis of viral RNA capping and RC assembly mediated by nsP1 and guides the development of antivirals targeting these essential steps of virus infection.